2022
DOI: 10.1186/s12935-022-02717-5
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between tumor-associated macrophages and tumor cells promotes chemoresistance via CXCL5/PI3K/AKT/mTOR pathway in gastric cancer

Abstract: Background 5-fluorouracil (5-FU)-based chemotherapy regimen has been widely used for the treatment of gastric cancer, but meanwhile the development of chemotherapeutic resistance remains a major clinical challenge. Tumor microenvironment (TME) frequently correlates with the development of chemoresistance in human cancer. As a major component of TME, the role of tumor-associated macrophages (TAMs) in the chemoresistance of gastric cancer has not been fully elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The activated M1 macrophage cell also secreted IL-1β [25]. CXCL5 could recruit monocytes to form M2-polarized macrophages, weaken the sensitivity of gastric cell line MNK-45 and HGC-27 to 5-FU [26]. With all these results, we could reasonably conclude that SLC7A2 was important in immune infiltration by regulating CXCL5 and IL-1β.…”
Section: Discussionmentioning
confidence: 60%
“…The activated M1 macrophage cell also secreted IL-1β [25]. CXCL5 could recruit monocytes to form M2-polarized macrophages, weaken the sensitivity of gastric cell line MNK-45 and HGC-27 to 5-FU [26]. With all these results, we could reasonably conclude that SLC7A2 was important in immune infiltration by regulating CXCL5 and IL-1β.…”
Section: Discussionmentioning
confidence: 60%
“…TIME contains different TIIC populations, which shows high relation to anticancer immune status within TME. Studies have shown that, as a kind of stroma cells, cancer-associated broblasts (CAFs) have the highest abundance in TME, and they are of cellular origin, phenotype and functional heterogeneities [28][29][30]. Shen [31]brie y summarize the roles of leukocytes and iron metabolism in tumorigenesis and their interaction in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MSR1 facilitated the polarisation of M2 TAMs by enhancing arginine and proline metabolism in macrophages 46 . Meanwhile, increased levels of chemokines in the TME, CXCL5, CXCL12 and CCL5, can induce a higher proportion of M2 TAMs 41,83,85 . The results of flow cytometry and immunohistochemistry of a transplanted tumour model indicated that EZH2 induced the polarisation of M2 TAMs 86 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 97%
“…162 Su et al found that patients with high infiltration of macrophages (CD68) were often related to poor response to neoadjuvant chemotherapy in a 103 sample cohort. 41 Meanwhile, high infiltration of M2 TAMs (CD206) was usually forecasted as resistant to trastuzumab therapy in patients with HER2-positive GC. 71 Sun et al reported that the high expression of total TAMs (CD68) or M2 TAMs (CD206) usually predicted a poor OS, while the high expression of M1 TAMs (CD86) indicated a better prognosis in HER2-positive patients with GC.…”
Section: The Relationship Between Tams and The Prognosis Of Patients ...mentioning
confidence: 99%